Competing Physiological Demands During Incipient Colony Foundation in a Social Insect: Consequences of Pathogenic Stress - Cole, Erin L.; Ilieş, Iulian; Rosengaus, Rebeca B. (Frontiers in Ecology and Evolution, 2018)
The social nature of termites has allowed them to become an ecologically dominant taxon. However, their nesting and foraging habits (decayed wood and/or soil), combined with frequent social interactions enhances the risk of pathogen transmission. New dispersing kings and queens are especially vulnerable to such pathogens due to the metabolic demands of nest construction, courtship, mating, oogenesis, and parental care, all while mounting an immune response to novel pathogens encountered upon leaving the natal nest. To quantify differential allocation of resources during colony establishment in response to disease exposure, Zootermopsis angusticollis kings and queens were paired after one or both individuals received an injection of saline, heat-killed Serratia marcescens (ecologically relevant, Gram-negative, soil bacterium), a sub-lethal dose of live S. marcescens, or were left untreated. We then quantified several indices of fitness, including the survival of the reproductive pair, onset and likelihood of oviposition, number of eggs produced, and egg quality as a function of parental immunological treatment. Our results uncovered complex and dynamic interactions between these fitness measures and pathogenic stress. Overall, pathogenic stress reduced the survival of kings and queens, the likelihood of oviposition and egg total, but not the onset of oviposition or egg quality, indicating that, in the face of disease, queens “opt” to maintain offspring quality over quantity. These impacts appear to be context-dependent – modulated by colony of origin, sex, mass, and the presence of a mate – rather than absolute. The acquisition of resources prior to colony foundation combined with the effects of pathogenic exposure, can dramatically limit the success of termites. Based on these empirical data, we have developed a conceptual model of the first 30-days of colony life, involving two successive fitness checkpoints, survival and oviposition, followed by an initial growth phase in which the first egg cohort is produced. In summary, we identified not only the intrinsic and extrinsic factors that influence successful termite colony foundation, but also the maternal and paternal pathogen-induced effects. Such effects alter resource allocation decisions of parents toward their offspring, with cascading consequences on colony fitness.